OPTIMALISASI UMKM MELALUI PENINGKATAN INOVASI DAN PEMASARAN PADA MASA PANDEMI DI DESA CIBEUREUM KECAMATAN CISARUA KABUPATEN BOGOR - Ismartaya Ismartaya; Ade Supriatna; Agung Ferdiansyah; Ari Nurpratomo; Asep Suryana; Ipat Latipah; Mohamad Hafid Zakaria; Muhammad Abian Nurdiansyah; Muhammad Syahrul Ramadhana; Siti Firda Parida; Pena Pena (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2021)
Optimization UMKM through increased innovation and marketing during the pandemic in Cibereum Village, Cisarua District, Bogor Regency (a case study on the "Gemblong" business group in Cibereum Village, Cisarua District, Bogor Regency). Development of increased innovation and digital marketing during the Covid 19 pandemic is carried out so that business players who The majority are classified as businesses that are threatened with closure due to the inability to spin capital money to carry out production, the price of raw materials is increasing but they do not have a stable market share. the tourism potential of the Puncak Bogor route. the incessant marketing through internet media, it is hoped that the name gemblong will stick as the Iconic Cibereum Village. Apart from being time efficient, this marketing medium is also known to be cost-effective. however, some entrepreneurs are constrained by limited human resources and facilities. to market the product.